Advertising Awareness dan Brand Equity pada Grabfood - Endrico Suciati, Nicolas; Erdiansyah, Rezi (Kiwari, 2024)
This very rapid technological progress is driving transformation and innovation in various fields. Many fields are experiencing changes caused by technological developments themselves, such as education, work, shopping, and the world of advertising. Grabfood is a food or beverage delivery service that has organizations in many countries and one of them is organized in Indonesia. A quantitative research method was used in the conduct of this study. The data collection technique itself was complete by delivering questionnaires for a survey to collect quantitative information. The population that the researchers used in this study were individuals who use the GrabFood application who live in West Jakarta. Sampling technique with purposive sampling. According to the findings of study, brand equity for Grabfood in West Jakarta is positively impacted by advertising awareness. Based on research findings conducted by the author, advertising awareness has a positive effect on Grabfood's Brand equity in West Jakarta. H1 is accepted and H0 is rejected, which means that there is an influence of Advertising Awareness on Grabfood's Brand Equity. And this means that the hypothesis formulated in this research can be accepted. From the discussion above, based on the results of research carried out by researchers, it is that advertising awareness has a positive effect on Grabfood's Brand equity in West Jakarta. Kemajuan teknologi yang sangat pesat ini mendorong transformasi dan juga inovasi-inovasi dalam berbagai macam bidang. Banyak sekali bidang yang mengalami perubahan yang di sebabkan dari perkembangan teknologi itu sendiri, seperti pendidikan, pekerjaan, perbelanjaan, maupun dunia periklanan. Salah satu layanan pesan-antar makanan dan minuman yang paling banyak diminati adalah Grabfood. berorganisasi di banyak negara dan salah satu nya berorganisasi di negara . Penelitian ini dilakukan menggunakan jenis penelitian kuantitatif. Teknik pengambilan data sendiri menyebarkan kuesioner sebagai bagian dari survei yang dilakukan untuk mengumpulkan data secara kuantitatif. Individu membentuk populasi yang peneliti gunakan untuk penelitian ini adalah pengguna aplikasi GrabFood yang berdomisili di Jakarta Barat. Teknik yang menggunakan purposive sampling sebagai metode sampel. Berdasarkan temuan penelitian yang telah dilakukan penulis adalah bahwa advertising awareness memiliki efek positif pada Brand equity Grabfood Di Jakarta Barat. H1 diterima dan H0 ditolak yang berarti terdapat pengaruh Advertising Awareness Terhadap Brand equity Grabfood. Dan artinya hipotesis yang dirumuskan pada penelitian ini dapat di terima. Dari pembahasan diatas, berdasarkan dari hasil penelitian yang sudah dikerjakan oleh peneliti, adalah bahwa advertising awareness memiliki efek positif pada Brand equity Grabfood Di Jakarta Barat.